Penerapan Algoritme Linear Regression untuk Prediksi Hasil Panen Tanaman Padi - Heru Wahyu Herwanto; Triyanna Widiyaningtyas; Poppy Indriana (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
Rice yields are very influential in meeting the basic food needs of rice. Because the needs of rice are always rising, it is necessary to predict crop yields to estimate the future planting to meet the basic food needs. The method used in this paper is linear regression algorithm, which can predict the yield of rice plants. The steps in this research are as follows: (1) data collection through surveys to farmers in Lamongan by giving questionnaires to respondents; (2) pre-processing the data, which is data cleaning; (3) applying linear regression to determine the strength of the relationship between one dependent or dependent variable and a set of independent or independent variables; and (4) results of the validation. Testing accuracy is carried out by measuring Root Mean Squared Error (RMSE). The average value of accuracy of the RMSE is 0. 432. This indicates that the variation of values produced by a forecast model is close to accurate, and results in the compatibility of the Multiple Linear Regression Model, with a reliability level of 94.51%.